ANALYSIS OF GREEN ECONOMIC VARIABLES ON THE INCOME OF COASTAL VILLAGE COMMUNITIES IN MALANG REGENCY - Maryunani, Maryunani; Jamal, Badrul (Unitri Press, 2024)
Green Economy is a new concept that is an extension of Sustainable Development. This concept has already been implemented by the Indonesian government, known as Environmentally Sustainable Development. The threat of climate change increasingly reduces the sustainability of the earth in meeting the needs and welfare of humanity. The increasingly modern economic development has the potential to negatively impact the environment. The emerging issues urgently require the implementation of Green Economy policies as the most effective environmental management control. This research aims to analyze the pillars of the green economy, namely Environment, Social, and Economic, in relation to the income of coastal village communities in Malang Regency. This research is exploratory in nature and uses descriptive analysis techniques. The analysis technique used in this study is SEM PLS data analysis with the SmartPLS 4 application. The results of this research indicate that economic factors such as the unemployment rate, price increases, and village economic growth have a significant contribution in determining the income of the Tambakrejo Village community. Efforts to increase community income are likely to succeed if the right economic policies or programs are implemented. Environmental Indicators on Community Income. This indicates that environmental factors, such as air quality, availability of clean water, or environmental sustainability, also play a role in influencing the income of the Tambakrejo Village community, although not as significantly as economic factors. Although its impact is not as significant as economic indicators, improving environmental conditions remains important. Social Indicators on Community Income. This indicates that social factors such as education, access to healthcare services, gender equality, and social security play a key role in determining the income levels of the community.